2018
DOI: 10.4103/1319-2442.235167
|View full text |Cite
|
Sign up to set email alerts
|

Primary IgA nephropathy in the Kashmiri population

Abstract: IgA nephropathy (IgAN) remains one of the most common glomerular lesions, which has a striking geographic distribution and is the most common form of primary glomerular disease in Asia. However, the exact prevalence or clinicopathological spectrum of IgAN in India is not well documented. This retrospective study analyzed the presentation in 126 patients of primary IgAN out of 298 native kidney biopsies (42.28%) performed over a period of three years (2013-2015). The patients were followed up for three months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…IgA nephropathy accounts for 40–47.2% of primary glomerular nephritis in China and is one of the most common primary glomerular diseases worldwide and an important cause of CRF (Wang et al, 2015; Wyatt & Julian, 2013). Our results indicated that 55.32% of IgAN patients have renal dysfunction, which is similar to the proportion of primary IgAN patients with renal failure in India (47%) (Chowdry et al, 2018). We also found that the VDR gene was closely related to elevated serum iPTH and P, and elevated iPTH and P were independent risk factors for renal dysfunction in IgAN.…”
Section: Discussionsupporting
confidence: 78%
“…IgA nephropathy accounts for 40–47.2% of primary glomerular nephritis in China and is one of the most common primary glomerular diseases worldwide and an important cause of CRF (Wang et al, 2015; Wyatt & Julian, 2013). Our results indicated that 55.32% of IgAN patients have renal dysfunction, which is similar to the proportion of primary IgAN patients with renal failure in India (47%) (Chowdry et al, 2018). We also found that the VDR gene was closely related to elevated serum iPTH and P, and elevated iPTH and P were independent risk factors for renal dysfunction in IgAN.…”
Section: Discussionsupporting
confidence: 78%
“…IgAN accounts for 40%-47.2% of primary glomerular nephritis in China and is one of the most common primary glomerular diseases worldwide and an important cause of CRF (Wang et al 2015; Wyatt & Julian 2013). Our results indicated that 55.32% of IgAN patients have renal dysfunction, which is similar to the proportion of primary IgAN patients with renal failure in India (47%) (Chowdry et al 2018). We also found that the VDR gene was closely related to elevated serum iPTH and P, and elevated iPTH and P were independent risk factors for renal dysfunction in IgAN.…”
Section: Discussionsupporting
confidence: 78%
“…Since this publication, other studies have added 295 patients, 274 of them receiving corticosteroids. One of them is the only prospective randomized study published to date, but it compared two forms of corticosteroid treatment, without an untreated control group 7 .…”
Section: Should Corticosteroids Be Employed To Treat Biopsy-proven Drug-induced Acute Interstitial Nephritis? Commentarymentioning
confidence: 99%